2009
DOI: 10.1007/s00216-009-3115-z
|View full text |Cite
|
Sign up to set email alerts
|

Determination of low-level ink photoinitiator residues in packaged milk by solid-phase extraction and LC-ESI/MS/MS using triple-quadrupole mass analyzer

Abstract: A confirmatory and quantitative method based on liquid chromatography-electrospray ionization tandem mass spectrometry (LC-ESI/MS/MS) has been developed for simultaneous determination of seven photoinitiator residues: benzophenone, (1-hydroxycyclohexyl)phenylketone (Irgacure 184), isopropylthioxanthone (ITX), 2-ethylhexyl-(4-dimethylamino)benzoate (EHA or EHDAB), 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone (Irgacure 907), (2,4,6-trimethylbenzoyl)diphenylphosphine oxide (TPO) and 2-benzyl-2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 19 publications
0
39
0
Order By: Relevance
“…A few methods based on LC in combination with UV detection (Papilloud et al 2002;Sanches-Silva et al 2008a, 2008b, 2009 or even fluorescence detection have also been reported (Morlock & Schwak 2006;Sagratini et al 2008). However, LC-MS/MS has gained popularity (Sagratini et al 2006;Bagnati et al 2007;Gil-Vergara et al 2007;Sun et al 2007;Allegrone et al 2008;Gallart-Ayala et al 2008, 2011Sanches-Silva et al 2008;Shen et al 2009). A comparison between GC and LC has shown, however, that both techniques are adequate: LC gives a lower LOQ while the repeatability is comparable (Gil-Vergara et al 2007).…”
Section: Introductionmentioning
confidence: 97%
“…A few methods based on LC in combination with UV detection (Papilloud et al 2002;Sanches-Silva et al 2008a, 2008b, 2009 or even fluorescence detection have also been reported (Morlock & Schwak 2006;Sagratini et al 2008). However, LC-MS/MS has gained popularity (Sagratini et al 2006;Bagnati et al 2007;Gil-Vergara et al 2007;Sun et al 2007;Allegrone et al 2008;Gallart-Ayala et al 2008, 2011Sanches-Silva et al 2008;Shen et al 2009). A comparison between GC and LC has shown, however, that both techniques are adequate: LC gives a lower LOQ while the repeatability is comparable (Gil-Vergara et al 2007).…”
Section: Introductionmentioning
confidence: 97%
“…GCeMS has been frequently used for the analysis of phthalates (Bononi & Tateo, 2009;Zhang et al, 2008) and PAH or MOAH (Biedermann & Grob, 2015;Bordajandi, Dabrio, Ulberth, & Emons, 2008;Chalbot, Vei, Lykoudis, & Kavouras, 2006), HPLCeMS/MS for bisphenols (Gallart-Ayala, Moyano, & Galceran, 2010;P erez-Palacios et al, 2012) and PFC (Begley et al, 2005Poothong et al, 2012;Trier et al, 2011), whereas ink photoinitiators have been analyzed by both techniques (Bugey et al, 2013;Sagratini et al, 2008;Shen, Lian, Ding, Xu, & Shen, 2009). Derivatization procedures were also developed for bisphenols and PFCA to make them amenable for GCeMS (Dufkov a, Cabala, & Sev cík, 2012;Viñas, Campillo, Martínez-Castillo, & Hern andez-C ordoba, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Shen et al 35) showed that photoinitiators can easily migrate from packaging to foods with a high fat content. The cytotoxicity of compounds like photoinitiators has been thought to be due in part to their hydrophobicity 36) since permeability through the phospholipid bilayer of cellular membranes increases with compound hydrophobicity.…”
Section: Discussionmentioning
confidence: 99%